2016
DOI: 10.1016/j.joen.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Toxicity Evaluation of Colloidal Silver Nanoparticles Used in Endodontic Treatments

Abstract: It was concluded that SNA and SNP were not cytotoxic at 25 μg/mL or lower concentrations. However, for safe clinical use, further studies establishing others points of its toxicologic profile are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…The silver nanoparticles may be associated with environmental toxicity due to their small size and variable properties, and the increased use of silver nanoparticles require assessment of environmental risks (Pan acek et al 2006, Sharma et al 2009, Gomes-Filho et al 2010, Rai et al 2012). Furthermore, the cytotoxicity of silver nanoparticles increases in higher concentrations and may be toxic to the host cells due to their small size, chemical composition, surface properties and nonspecific oxidative damages (Kim et al 2009, Gomes-Filho et al 2010, Rai et al 2012, Shrestha & Kishen 2016, Takamiya et al 2016. Biofilms are made up of an extracellular polysaccharide matrix (Rai et al 2012), and microorganisms in mature biofilms are notoriously difficult to eradicate and can be extremely resistant (Mohammadi & Abbott 2009, Kishen 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The silver nanoparticles may be associated with environmental toxicity due to their small size and variable properties, and the increased use of silver nanoparticles require assessment of environmental risks (Pan acek et al 2006, Sharma et al 2009, Gomes-Filho et al 2010, Rai et al 2012). Furthermore, the cytotoxicity of silver nanoparticles increases in higher concentrations and may be toxic to the host cells due to their small size, chemical composition, surface properties and nonspecific oxidative damages (Kim et al 2009, Gomes-Filho et al 2010, Rai et al 2012, Shrestha & Kishen 2016, Takamiya et al 2016. Biofilms are made up of an extracellular polysaccharide matrix (Rai et al 2012), and microorganisms in mature biofilms are notoriously difficult to eradicate and can be extremely resistant (Mohammadi & Abbott 2009, Kishen 2012.…”
Section: Discussionmentioning
confidence: 99%
“…With a focus on their antimicrobial effects, they have been incorporated into bonding agents and restorative materials to prevent biofilm formation and reduce caries (Durner et al 2011, Garcia-Contreras et al 2011, Cheng et al 2012, orthodontic adhesives (Ahn et al 2009, Degrazia et al 2016) and into implant materials (Sheikh et al 2010, Allaker & Memarzadeh 2014. Silver nanoparticles have been tested as endodontic irrigants and intracanal medicaments (Wu et al 2014, Abbaszadegan et al 2015, added to calcium hydroxide as a vehicle (Javidi et al 2014, Afkhami et al 2015, incorporated into endodontic filling materials (Mohamed Hamouda 2012, Correa et al 2015 and calcium silicate cements (Bahador et al 2015, Vazquez-Garcia et al 2016, and have shown lower levels of cytotoxicity (Gomes-Filho et al 2010, Takamiya et al 2016. Silver nanoparticles have been tested as endodontic irrigants and intracanal medicaments (Wu et al 2014, Abbaszadegan et al 2015, added to calcium hydroxide as a vehicle (Javidi et al 2014, Afkhami et al 2015, incorporated into endodontic filling materials (Mohamed Hamouda 2012, Correa et al 2015 and calcium silicate cements (Bahador et al 2015, Vazquez-Garcia et al 2016, and have shown lower levels of cytotoxicity (Gomes-Filho et al 2010, Takamiya et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Investigators have affirmed the noncytotoxicity of ammonia and PVPs stabilized AgNPs at lower concentrations in mice. 47 Nonetheless, AgNPs damaged DNA and caused in vitro toxicity and functional impairment in human cell lines in other studies. 48,49 Some researchers studied the short- and long-term effects of AgNPs on human microvascular endothelial cells and suggested that their cytotoxicity and genotoxicity makes them a useful tool to control excessive angiogenesis.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 96%
“…In the last several years, many authors have examined the toxicity of inorganic NPs in cultured cell lines and in animal models [42][43][44]. Several factors must be tracked in the case of inorganic NPs cytotoxicity: the first step is represented by in vitro studies that are essential for screening the toxicological effects of NPs on cultured cells.…”
Section: Collagen-inorganic Nanoparticles Compositesmentioning
confidence: 99%